3(n + 3) = -4n + 30

1 answer

To solve the equation \(3(n + 3) = -4n + 30\), follow these steps:

  1. Distribute the 3 on the left side:

    \[ 3n + 9 = -4n + 30 \]

  2. Next, combine like terms. Add \(4n\) to both sides to get all the \(n\) terms on one side:

    \[ 3n + 4n + 9 = 30 \]

    This simplifies to:

    \[ 7n + 9 = 30 \]

  3. Now, subtract 9 from both sides to isolate the term with \(n\):

    \[ 7n = 30 - 9 \]

    Which simplifies to:

    \[ 7n = 21 \]

  4. Finally, divide by 7 to solve for \(n\):

    [ n = \frac{